Is Ethereum better explained by Bitcoin and Ripple prices? An ECM approach on the covid-19 episode price data. (7th January 2021) - Kumar, S. Santhosh
Bitcoin, Ethereum and Ripple are the three major cryptocurrencies with market capitalisation exceeding 70% of all the cryptos. The covid-19 threats since the beginning of the 2020 are disturbing the financial markets all around the world. This study is an enquiry to model the fluctuations among the three cryptocurrencies with the hypothesis that whether a combination of two coins could explain the changes in the other coin. The study found that Bitcoin and Ripple are better explaining the Ethereum returns in the short-run. The negative error correction coefficient found in the regression indicates that if the daily log returns of ETH is above that of the daily log return of BTC by one point, the daily log return of ETH fall by 1.11 point. On the other hand, the positive error correction coefficient indicates that if the daily log return of ETH is above that of the daily log return of XRP by one point, the daily log return of ETH increases by 0.14 point.